Lipidation of the LC3/GABARAP family of autophagy proteins relies upon a membrane curvature-sensing domain in Atg3 - Nath, Sangeeta (2014)
The protein biochemistry supporting autophagosome growth on the cup-like isolation membrane is likely different from the biochemistry on the closed and maturing autophagosome. Thus, the highly curved rim of the cup may serve as a functionally-required surface for transiently-associated components of the early-acting autophagic machinery. Here we demonstrate that the E2-like enzyme, Atg3, facilitates LC3/GABARAPlipidation only on membranes exhibiting local lipid-packing defects. This activity requires an amino-terminal amphipathic helix similar to motifs found on proteins targeting highly curved intracellular membranes. By tuning the hydrophobicity of this motif, we can promote or inhibit lipidation in vitro and in rescue experiments in Atg3 knockout cells, implying a physiologic role for this stress detection. The need for extensive lipid-packing defects suggests that Atg3 is designed to work at highly-curved membranes perhaps including the limiting edge of the growing phagophore.